PETROGRAPHIC STUDIES OF LIMESTONE IN DUKAMAJE FORMATION AT GILBEDI, GADA, SOKOTO BASIN, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2022)
The study was conducted in and around Gilbedi village and its environs in the Iullemmeden Basin, Sheet 4 SW, Gada local government area, Sokoto, North-West Nigeria. The research area is located in the Sokoto Basin, which is part of the Iullemmeden Basin. The study area is bounded by latitudes 13046'05"N to 13043'22"N and longitudes 5045'00"E to 5040'45"E covering 25 Km2. The mapping exercise was carried out using a topographic base map on a scale of 1:25,000. The observed Dukamaje Formation is derived from a marginal marine depositional setting and is primarily composed of shales, limestones, and mudstone with gypsum intercalation. Shales are consolidated mudstones with a fine-grained texture which is greyish. Limestone is medium to coarse-grained. It is a pale yellow to greyish in color. Petrographic observation showed the grains to be equigranular, and having interstitial quartz cement. The quartz occurs as colorless anhedral crystal with no alteration but with wavy extinction and without cleavage. Other minerals present include muscovite. Based on Folk’s classification for limestone, the limestone in the study area is called “extramicrite” because the allochems are extraclasts. The limestone also lime mud supported which is less than 10% of grains Based on Dunham’s classification schemes for limestone, the limestone of the studied Dukamaje Formation is a “mudstone”.
Keywords: Allochem; Dukamaje; Micrite; Limestone